2010
DOI: 10.1111/j.1465-3362.2010.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug-dependent inpatients reporting continuous absence of spontaneous drug craving for the main substance throughout detoxification treatment

Abstract: Drug -dependent inpatients who report absence of craving are characterised by relatively low levels of depression and anxiety throughout detoxification treatment, and relatively low levels of trait anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
1
8
0
1
Order By: Relevance
“…Therefore, it is likely that within the context of long-term treatment centers, craving may be a psychological dimension of substance dependence that is more difficult to assess using a questionnaire and/or manipulate by exposure to drug-associated stimuli. This is consistent with low levels of spontaneous craving described within inpatient addiction units for alcohol and cocaine dependence (see [64] for review).…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, it is likely that within the context of long-term treatment centers, craving may be a psychological dimension of substance dependence that is more difficult to assess using a questionnaire and/or manipulate by exposure to drug-associated stimuli. This is consistent with low levels of spontaneous craving described within inpatient addiction units for alcohol and cocaine dependence (see [64] for review).…”
Section: Discussionsupporting
confidence: 86%
“…24 Indeed, mopiate receptor availability in the ventral striatum in abstinent alcoholic patients has been shown to be correlated with craving for alcohol and an important risk factor for relapse. 25 Studies have also found an association between HA and craving among drug, 26 tobacco, 10 and alcoholdependent individuals. 27,28 Among cigarette smokers, subjects with high HA experience greater abstinenceinduced increases in irritability, anxiety, restlessness, and depression.…”
Section: Discussionmentioning
confidence: 98%
“…De Los Cobos et al (2011) show that referral to inpatient treatment contributes to an improvement of psychiatric symptoms (decreasing anxiety and depression), and a decrease in the number of subsequent visits to the emergency services. The present study did not show any correlation of referral to inpatient treatment and changes in the number of subsequent visits to the emergency psychiatric unit.…”
Section: Discussionmentioning
confidence: 99%